Mobilities of labour and capital in Asia - Aulakh, Preet S., 1962-; Kelly, Philip F., 1970- (Cambridge : Cambridge University Press, 2020)
This book explores the mobilities of capital and labour in the contemporary global economy, with a particular focus on Asia. Using an analytical framework around three dimensions related to the forms, institutions, and spatialities of mobility, the chapters use a variety of sub-national, national and transnational sites within and beyond Asia to examine the interrelationships between mobilities of capital and labour at multiple levels of analyses. The book foregrounds the intricate and persistent linkages between the two mobilities, which have played an important role in capitalist development, but have hitherto mostly been analyzed as separate processes.
Conceptualizing labour and capital mobilities in Asia / Preet S. Aulakh and Philip Kelly -- Offshore spaces, multi-scalar bordering processes and the segmented mobilities of capital and labour in Asia / Jana M. Kleibert -- Japanese MNCs and the control of overseas direct investments : expatriates, foreign employees and Japan's soft power / Harald Conrad and Hendrik Meyer-Ohle -- Accumulation at the margins? Mineral brokerage and Chinese investments in Philippine mining / Alvin A. Camba -- Soft power and transnationalism affecting capital and labour mobility : Chinese diaspora in Mexico and Peru / Francisco J. Valderrey, Miguel A. Montoya and Mauricio Cervantes -- The spatial decoupling and recombination of capital and labour : understanding the new flows across the China-Southeast Asia borderlands / Xiangming Chen, Na Fu, Sam Zhou and Gavin Xu -- Skills development initiatives and labor migration in a secondary circuit of globalization of production : evidence from the garment industry in India / Asha Kuzhiparambil -- The counter geographies of globalization : women's labour migration along the Nepal-Persian Gulf migratory corridor / Hari KC -- Migration and developmental capital in a Punjab village / Rosy Hastir -- The production of nurses for global markets : tracing capital and labour circulation in and out of Asia / Margaret Walton-Roberts -- The mobility-oligopoly nexus in Philippine property development / Kenneth Cardenas.
Title from publisher's bibliographic system (viewed on 10 Jan 2020).
Keywords: Labor mobility -- Asia; Capital movements -- Asia; Globalization -- Economic aspects -- Asia; International economic relations